Conflict and Tolerance in Urban Outdoor Recreation: A case study in Antalya and Berlin - Sayan, Selcuk; Kalisch, Dennis (Turizam, 2018)
Europe has become ‘a continent of immigration’ in the course of the last half century, and European societies have experienced growing ethnic and cultural diversity. Accordingly diverse social groups with various cultural backgrounds interact in everyday life. In this context, urban green spaces (UGS) provide opportunities and places for recreation, stress relief, interaction and encounters with other people. In contrast to a dense built environment of the cities, parks can be a platform for breaking social segregation. Personal characteristics of the users or visitors including cultural and socio-demographic background have been found to have an influence on outdoor recreation use patterns. Immigrants participate in recreation activities, but sometimes in different ways than members of the host community due to their diverse habits, preferences and different behaviour. However, little is known about these differences in recreation patterns in the urban environment particularly in continental Europe. Thus, the objective of the study is to a) explore urban outdoor recreation patterns of immigrants, b) investigate the interrelation between cultural background and recreation patterns and c) analyse the role of UGS for visitors’ encounters of different migration background in Antalya, Turkey and Berlin, Germany. Findings from qualitative interviews in both cities demonstrate that tolerance is the precondition for a successful integration into the host society. Respondents agreed that green spaces have a high potential for supporting the social integration process. Language can be a barrier for interaction and common interests are needed as a starting point. They agreed that the host community in both cities have a high willingness to accept foreigners.